Regulatory and Legal Pressures and the Costs of Nasdaq Trading - Schultz, Paul (Review of Financial Studies, 2000)
Journal Article Regulatory and Legal Pressures and the Costs of Nasdaq Trading Get access Paul Schultz Paul Schultz University of Notre Dame Address correspondence to Paul Schultz, College of Business Administration, University of Notre Dame, Notre Dame, IN 46556, or e-mail: Paul.H.Schultz.19@nd.edu. Search for other works by this author on: Oxford Academic Google Scholar The Review of Financial Studies, Volume 13, Issue 4, October 2000, Pages 917–957, https://doi.org/10.1093/rfs/13.4.917 Published: 15 June 2015